Focus on the future: Episodic future thinking reduces discount rate and snacking - Dassen, Fania C.M.; Jansen, Anita; Nederkoorn, Chantal; Houben, Katrijn (Appetite, 2016)
Obesity seems related to a preference for immediate gratification. By changing this focus on short term benefits to a more future-oriented outlook, delay discounting (impulsive decision making) can be changed by a manipulation of episodic future thinking (EFT). EFT comprises a vivid mental simulation of general future experiences. EFT may also affect consumption of unhealthy foods, which can be seen as a choice for immediate gratification. Recent research shows that future orientation should be tailored to the behavior at outcome. We therefore hypothesize that the effectiveness of EFT on food intake could be enhanced by making the content food-related. We conducted a 2 (future vs past thinking) by 2 (food vs non-food related thoughts) between-subject design experiment in female undergraduates (N = 94), to compare the efficacy of EFT versus the recalling of episodic past events in reducing discount rate and caloric intake. Content of imagery was either unrestricted or food-related. Participants engaged in EFT or control episodic imagery while snacks were offered to freely consume, and next the Monetary Choice Questionnaire was completed as a measure of delay discounting, while again being engaged in EFT or control imagery. Both types of EFT reduced delay discounting, however, only food-related EFT lead to more restricted caloric consumption. Thus, we found evidence that EFT reduced discount rate during decision making. However, in order to restrict caloric intake, EFT should entail food-related imagery. As discount rate and caloric intake were not related in the current sample, the underlying mechanism remains to be discovered. Results however suggest that EFT is a promising technique to resist immediate gratification. •Episodic future thinking (EFT) during decision making reduced delay discounting.•We explored the beneficial effect of food-related EFT.•Only food-related EFT influenced caloric intake.•Outcome measures of discount rate and caloric intake were not related.•The underlying mechanism for reduced caloric intake remains unclear.